Improved electroporation efficiency of intact Lactococcus lactis subsp. lactis cells grown in defined media. - McIntyre, D A (1989)
The impact of growth conditions on electroporation of Lactococcus lactis subsp. lactis LM0230 (previously designated Streptococcus lactis LM0230) was evaluated. Cells grown in M17 broth supplemented with 0.5% glucose (M17-Glu) and two chemically defined synthetic media, FMC and RPMI 1640, all supplemented with 0.24% DL-threonine or 0.5% glycine, were harvested, washed with double-distilled water, diluted, and porated in the presence of 1 microgram of pGB301 DNA with a Transfector 100 (BTX, Inc., San Diego, Calif.) or a Gene Pulser (Bio-Rad Laboratories, Richmond, Calif.). Transformants were recovered at consistently higher efficiencies for cells grown in FMC or RPMI 1640 (10(3) to 10(4) transformants per micrograms of DNA) than for cells grown in M17-Glu (10(1) to 10(2) transformants per micrograms of DNA). Other parameters influencing electroporation of L. lactis cells grown in chemically defined media were growth phase and final concentration of cells, concentration of plasmid DNA, voltage achieved during poration, and expression conditions. A high degree of variability in transformation efficiencies was evident for replicate samples of cells pulsed with either electroporation machine. A trend toward decreased variability was observed for duplicate samples of cells prepared on the same day. In addition, storage studies done with a large batch of cells prepared on the same day indicated that freezing dry cell pellets at -60 degrees C had no deleterious effect on transformation efficiencies over a 30-day period when a new 0.2-cm cuvette was used for porating each sample.